Welding dynamics in an atomistic model of an amorphous polymer blend with polymer–polymer interface. Issue 15 (3rd June 2020) - Luchinsky, Dmitry G.; Hafiychuk, Halyna; Hafiychuk, Vasyl; Chaki, Kenta; Nitta, Hiroya; Ozawa, Taku; Wheeler, Kevin R.; Prater, Tracie J.; McClintock, Peter V. E.
Abstract: We consider an atomistic model of thermal welding at the polymer‐polymer interface of a polyetherimide/polycarbonate blend, motivated by applications to 3D manufacturing in space. We follow diffusion of semiflexible chains at the interface and analyze strengthening of the samples as a function of the welding time t w by simulating the strain–stress and shear viscosity curves. The time scales for initial wetting, and for fast and slow diffusion, are revealed. It is shown that each component of the polymer blend has its own characteristic time of slow diffusion at the interface. Analysis of strain–stress demonstrates saturation of the Young's modulus at t w  = 240 ns, while the tensile strength continues to increase. The shear viscosity is found to have a very weak dependence on the welding time for t w  > 60 ns. It is shown that both strain–stress and shear viscosity curves agree with experimental data. Abstract : Welding dynamics and strengthening of the interface in the polyetherimide blend are analyzed using molecular dynamics. Time scales for initial welding of blend components are revealed. The strengthening is characterized by the strain‐stress and shear viscosity curves obtained at different welding times. A way to control welding time in 3D manufacturing is proposed. The revealed features of the dynamics of semiflexible polymer chains are of importance for theoretical developments and practical applications.